Legal Responsibility and Accountability of the Medical Profession Within the Framework of Ministry of Health Regulation No. 3 of 2025: Challenges and Opportunities - Mohamad Ihsan Ramdani (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
This article examines legal liability and professional accountability in the medical profession within the framework of Regulation of the Minister of Health Number 3 of 2025, with particular emphasis on the establishment and authority of the Medical Professional Disciplinary Council (Majelis Disiplin Profesi/MDP). This study employs a normative legal approach by analyzing statutory regulations, legal doctrines, and relevant scholarly literature in the fields of health law and professional discipline. The findings indicate that Regulation of the Minister of Health Number 3 of 2025 has normatively established a more structured regime of medical professional discipline through a clear separation between disciplinary mechanisms and criminal as well as civil liability mechanisms. The MDP is positioned as a specialized administrative body tasked with safeguarding professional standards and ensuring the accountability of medical practitioners, supported by procedural rules and types of sanctions designed to guarantee procedural justice. This regulatory framework is consistent with theories of professional accountability and legal certainty with , although it continues to present normative challenges, particularly concerning appeal mechanisms and inter-institutional coordination among law enforcement bodies. This article contributes to the development of health law scholarship by offering an institutional and systemic analysis of medical professional discipline and by providing a conceptual foundation for policy refinement and future research on the implementation of medical professional accountability in Indonesia.